2019
DOI: 10.31486/toj.18.0178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Transcatheter vs Surgical Aortic Valve Replacement in Patients With Chronic Liver Disease: A Systematic Review and Metaanalysis

Abstract: Background: Chronic liver disease increases cardiac surgical risk, with 30-day mortality ranging from 9% to 52% in patients with Child-Pugh class A and C, respectively. Data comparing the outcomes of transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR) in patients with liver disease are limited. Methods: We searched PubMed, Cochrane Library, Web of Science, and Google Scholar for relevant studies and assessed risk of bias using the Risk of Bias in Non-Randomized Studies-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The latter finding might also be linked to the significantly lower rate of postprocedural atrial fibrillation observed in TAVR patients (31.5 vs. 48.2%, p < .01) and the consequent need for long-term anticoagulation, which poses ELSD patients at high risk for short and long-term bleeding events. The better prognosis of TAVR patients confirms the findings of a recent metaanalysis pooling data of patients with chronic liver disease, showing a significantly lower in-hospital mortality for subjects receiving TAVR as compared with SAVR (7.2 vs. 18.1%; OR 0.67; 95% CI 0.25, 1.82) 2.…”
supporting
confidence: 82%
“…The latter finding might also be linked to the significantly lower rate of postprocedural atrial fibrillation observed in TAVR patients (31.5 vs. 48.2%, p < .01) and the consequent need for long-term anticoagulation, which poses ELSD patients at high risk for short and long-term bleeding events. The better prognosis of TAVR patients confirms the findings of a recent metaanalysis pooling data of patients with chronic liver disease, showing a significantly lower in-hospital mortality for subjects receiving TAVR as compared with SAVR (7.2 vs. 18.1%; OR 0.67; 95% CI 0.25, 1.82) 2.…”
supporting
confidence: 82%
“…In fact, as compared to SAVR, patients undergoing TF‐TAVR were older (76.5 ± 9.5 vs. 71.6 ± 7.9 years, p = .020) and at higher baseline surgical risk (STS‐PROM 4.5 ± 6.6 vs. 2.0 ± 2.8%, p < .01). Moreover, while this report was not sufficiently powered to detect a statistically significant difference in perioperative mortality, in a recent meta‐analysis pooling data of patients with chronic liver disease, in‐hospital mortality was lower for those receiving TAVR as compared to SAVR (7.2% vs. 18.1%; OR = 0.67; 95% CI [0.25, 1.82]) …”
Section: Factors That Might Be Considered By the Heart Team For The Dmentioning
confidence: 80%
“…[14][15][16][17][18] In comparison with TAVR, SAVR was associated with increased procedural related morbidities. A recent pooled analysis 19 including coagulopathy, increased risk of infection, fluid and electrolyte shifts, with limited respiratory and renal reserve, they are very likely to benefit from less invasive option provided by TAVR. [21][22][23] Therefore, in conclusion, our study supports TAVR is a safe option and a viable treatment options for aortic valve stenosis in patients with ESLD.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with TAVR, SAVR was associated with increased procedural related morbidities. A recent pooled analysis of clinical outcomes found significantly lower odds of in‐hospital, blood transfusion and periprocedural hospital length of stay, reduced cost of hospitalization, and reduced acute kidney injury in TAVR as compared to SAVR in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%